Balimau Tradition in the Wedding Procession in Nagari Koto Alam, Pangkalan Koto Baru District, Limapuluh Kota Regency, West Sumatra Province - Erlinda, Rilda Yunisa; Endrizal; Kahanna , Mutia (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study examines the "Balimau Tradition in the Wedding Procession in Koto Alam Village, Pangkalan Koto Baru District, Lima Puluh Kota Regency, West Sumatra Province". The purpose of this study is to describe the implementation of the balimau tradition in the wedding procession in Koto Alam Village and to describe the meaning of the balimau tradition. The theory used in this study is the symbolic interpretative theory of Clifford Geertz. The method used in this study is a qualitative method. Data collection in this study was carried out using observation, interview, and documentation methods. The data analysis technique in this study uses steps including data reduction, data presentation, and drawing conclusions and verification. The results of this study indicate that the balimau tradition is a bathing tradition carried out by the bride and groom after carrying out the marriage contract, this tradition is carried out during the village barolek event. The implementation of the balimau tradition is to prepare the tools and materials for balimau, the bride and groom are paraded to the river, read prayers, shave the bride's hair, rub the boreh kasai on the bride and groom, rub the bungo kiambai, the bride and groom dive, wash the bride and groom's hair, bathe, use pamanih oil, distribute kotan kuniang, and wash away the remaining materials from the balimau tradition. The meaning contained in the balimau tradition is to cleanse and purify the bride and groom. The tools and materials used in the balimau tradition have meanings that are intended for the good of the bride and groom.